Photocatalytic oxidation technology for indoor air pollutants elimination: A review. (October 2021) - Li, Yu-Wei; Ma, Wan-Li
Abstract: As more people are spending the majority of their daily lives indoors, indoor air quality has been acknowledged as an important factor influencing human health, with increasing research attention in recent decades. Indoor air pollutants (IAPs), such as volatile organic compounds (VOCs) and semi-volatile organic compounds (SVOCs), can cause acute irritation and chronic diseases. Photocatalytic oxidation (PCO) technology is an efficient approach for eliminating IAPs. In this review, the development of PCO technology was explained and discussed to promote future development of PCO technology for IAP elimination. First, the health effects and the measured concentrations of typical VOCs and SVOCs in indoor environments worldwide were briefly introduced. Subsequently, the development and limitations of some typical photocatalytic reactors (including packed-bed reactors, monolithic reactors, optical fiber reactors, and microreactors) were summarized and compared. Then, the influences of operating parameters (including initial concentration of contaminants, relative humidity, space velocity, light source and intensity, catalyst support materials, and immobilization method) and the degradation pathways as well as intermediates of PCO technology were elucidated. Finally, the possible challenges and future development directions regarding PCO technology for IAP elimination were critically proposed and addressed. Graphical abstract: Image 1 Highlights: Semi-volatile organic compounds are common indoor air pollutants (IAPs). Photocatalytic oxidation technology is an eﬀective technology for IAPs elimination. Development of photocatalytic reactors are summarized and compared. Influence of operating parameters on photocatalytic oxidation efficiency is reviewed. Intermediates and degradation pathways of IAPs are elucidated.